Social and Economic Significance of Moral Capital - Wódka, Marek (Annales. Etyka w Życiu Gospodarczym, 2018)
In recent years, or even months, Polish scholars have gradually become more and more interested in moral capital. Generally, they have addressed this issue without going into much detail. Building on the latest publications which describe moral capital, this paper thoroughly explores the issue of the social and economic significance of moral capital. As a result, moral capital will be presented from two complementary points of view, namely sociological and economic.